Sistem Informasi Geografis Pemetaan UMR Pegawai dan Persebaran Industri Jawa Tengah Tahun 2023 Berbasis WebGIS - Kikit Wahyuni; Bambang Agus Herlambang; Ahmad Khoirul Anam (JOURNAL SAINS STUDENT RESEARCH, 2026)
The Regonal Minimum Wage (UMR) is a crucial indicator for assessing worker welfare and its determination is influenced by factors such s economic growth, inflation, and the need for a decent living. In Central Java Province, the industrial sector is a key economic pillar, yet differences in UMR values exist between districts/cities, leading to disparities in welfare. To address this, a Geographic Information System (GIS) is an effective solution, as it visualizes UMR data in the form of ineractive thematic maps that demonstrate distribution patterns and spatial relationships between regions. Through this mapping, the government, industry players, and the public can conduct more targeted analyses for economic and employment planning. In addition to its practical benefits, GIS use also provides educational value for students in understanding the application of geospastial technology to socio-economic issues. Overall, GIS-based UMR mapping in Central Java is expected to provide faster, more accurate, and more transparent information to various parties.